2004
DOI: 10.1002/mop.11367
|View full text |Cite
|
Sign up to set email alerts
|

A new method for load matching in multimode‐microwave heating applicators based on the use of dielectric‐layer superposition

Abstract: 8510C Network Analyser. Figures 3 and 4 show the measured radiation patterns in the d-a-b and d-b-a orientations of the DR.The patterns of all the orientations are reasonably broad in both E and H planes. The cross-polarization is ϳ 20 dB, indicating the usefulness of the proposed antenna configuration for mobile communication. It is observed that the gain of the proposed antenna configuration is almost the same as that of a standard circular patch antenna with Ϯ 0.5-dB variation. CONCLUSIONExperiments were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…This differs from the procedure carried out in [19] since, in that study, these dielectric layers were employed in order to optimize load matching. Previous studies [20]- [22] use this configuration as a matching technique as well, and good results were obtained there with efficiencies above 95%. Other studies use dielectric susceptors as a form of active packaging in order to modify temperature profiles when using microwave heating [23].…”
Section: Introductionmentioning
confidence: 95%
“…This differs from the procedure carried out in [19] since, in that study, these dielectric layers were employed in order to optimize load matching. Previous studies [20]- [22] use this configuration as a matching technique as well, and good results were obtained there with efficiencies above 95%. Other studies use dielectric susceptors as a form of active packaging in order to modify temperature profiles when using microwave heating [23].…”
Section: Introductionmentioning
confidence: 95%
“…In a previous work, a novel load-matching method based on the use of dielectric-layer superposition around a sample was presented, tested, and validated for a multimode microwave-heating cavity [1]. An iterative procedure was implemented to find the best dielectric multilayer configuration for a given dielectric load.…”
Section: Introductionmentioning
confidence: 99%
“…Common problems of all those methods are the high sensibility 2 to the variation of the dielectric properties, and shape and dimensions of the sample to be heated. Other authors have shown that it is possible to achieve high power efficiencies by using dielectric casts around the sample [3,4]. However, these methods have not been experimentally tested yet, showing only simulated data.…”
Section: Introductionmentioning
confidence: 99%